Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.aop.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocality and entanglement via the Unruh effect

Abstract: Modeling the qubit by a two-level semiclassical detector coupled to a massless scalar field, we investigate how the Unruh effect affects the nonlocality and entanglement of two-qubit and threequbit states when one of the entangled qubits is accelerated. Two distinct differences with the results of free field model in non-inertial frames are (i) for the two-qubit state, the CHSH inequality can not be violated for sufficiently large but finite acceleration, furthermore, the concurrence will experience "sudden de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Based on the model of two‐level detector qubit coupled to a massless scalar field, we have discussed how the Unruh effect affects the quantum coherence of tripartite W state and GHZ state when one of the entangled qubits is in a accelerated setting. The Unruh–Dewitt detector model avoids the problems suffered by free field model, which is more physical and corresponds to the reality further . The results indicated that Unruh thermal noise really destroys the tripartite quantum resources.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on the model of two‐level detector qubit coupled to a massless scalar field, we have discussed how the Unruh effect affects the quantum coherence of tripartite W state and GHZ state when one of the entangled qubits is in a accelerated setting. The Unruh–Dewitt detector model avoids the problems suffered by free field model, which is more physical and corresponds to the reality further . The results indicated that Unruh thermal noise really destroys the tripartite quantum resources.…”
Section: Discussionmentioning
confidence: 85%
“…Due to the difficulty in observing Unruh effect, researchers employ the semiclassical Unruh–Dewitt detector model, which interacts locally with the neighboring external field. Afterward, much interests have been triggered by the behaviors of quantum entanglement, quantum discord, quantum coherence, and quantum nonlocality of the entangled detectors under the influence of Unruh thermal noise. However, we notice that the above investigations are mainly confined to a two‐detector system, and the character of multipartite even N ‐qubit system is still under study.…”
Section: Introductionmentioning
confidence: 99%
“…Here, in particular, we study the Unruh effect [10,11,16] which predicts thermal like effects from observing uniform acceleration of the Minkowski vacuum. This has attracted intense interest [17][18][19][20][21][22][23][24][25][26][27] and has emerged as a natural quest in the direction of relativistic quantum information [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Jhep02(2017)082mentioning
confidence: 99%
“…The model can be considered as follows: a pair of observers, Alice and Bob, where each of them has a semiclassical Unruh–Dewitt detector modeling via a two‐level noninteracting atom with a fixed energy gap Ω (Ω>0) . The detectors initially share an entangled state as |ψAB=cosθ|01AB+sinθ|10ABwhere false|0false⟩Afalse(Bfalse) and false|1false⟩Afalse(Bfalse) denote the unexcited and excited states of Alice's or Bob's detectors, respectively.…”
Section: Model Of the Detector‐field Interactionmentioning
confidence: 99%
“…The famous Unruh effect manifests that a uniformly accelerated detector which interacts with external fields becomes excited in the Minkowski vacuum and the quantum properties of fields is observer dependent . Many researches have been focused on the influence of the Unruh effect on quantum systems in an accelerated setting, which demonstrate that the quantity of quantum resources such as entanglement, nonlocality, and coherence appear a degradation from the viewpoint of noninertial observers owing to the Unruh thermal bath.…”
Section: Introductionmentioning
confidence: 99%